EFFECT OF FRYING TEMPERATURE OF SWEET POTATO CHIPS ON VACUUM FRYING TYPE VACUUM PUMP - Dewi Sartika T; S. B. Daulay; A. Rohanah (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2019)
Food processing with cooking needs a special way to keep the content of the nutrition of the food. This research aimed to test the temperature Frying of sweet potato chips in vacuum frying (vacuum pump type). Therefore, research had been conducted using factorial randomized block design with one factor, i.e., frying temperature (75 °C, 85 °C, and 95 °C). Parameters observed were loss of oil, water content, and organoleptic values. The results showed that temperature significantly affected the loss of oil, water content, and organoleptic value. The best result was found in the frying temperature of 95 °C.